Projections of flood regime changes over the upper-middle Huaihe River Basin in China based on CMIP6 models - Bian, Guodong; Zhang, Jianyun; Song, Mingming; Qian, Xin; Guan, Tiesheng; Wang, Guoqing (Frontiers in Environmental Science, 2023)
Climate change is altering the hydrological cycle to different extents, in particular for intensification of extreme precipitation and floods, which has garnered more attention as a significant scientific issue in the last few decades. The last Coupled Model Inter-comparison Project 6 (CMIP6) has designed with new shared socioeconomic pathway scenarios (SSPs) to combine the socioeconomic development with greenhouse gas emissions to project future climate. In this study, we use 22 global climate models (GCMs) from CMIP6 to investigate the future variations of extreme precipitation and temperature under SSP2-4.5 and SSP5-8.5 scenarios over the upper middle Huaihe River basin (UMHRB). Then the modified Xinanjiang model integrating the flood control module is driven to obtain projections of daily streamflow, and to evaluate the future variations of flood regimes. Results show that: (1) the characteristics of future extreme precipitation, such as the average intensity and amount of annual precipitation and extreme precipitation, are projected to increase, and average, maximum and minimum temperature also display substantial increasing trends in the future over the UMHRB; (2) the warmer climate will lead to more severe the flood magnitude under SSP5-8.5 scenario during the far future period (2071-2100) over the UMHRB. The results of multi-model ensemble show that the annual maximum flood peaks (15-days flood volumes) of Wangjiaba and Wujiadu station are projected to increase 46.4%(43.1%) and 45.4% (51.1%), respectively, in the far future (2071-2100) under SSP5-8.5 scenario.(3) variations in flood frequency tend to resemble variations in flood magnitude, and the return period of design flood will obviously decrease under future climate scenarios. For instance, in the far future period, under SSP5-8.5 scenarios, the return period of design flood with 100-year return period will become 38-year and 31-year for Wangjiaba and Wujiadu stations, respectively. The study enhances a more realistic understanding that the occurrence of future extreme precipitation and floods are projected to be more frequent and severe, thereby an urgent imperative to develop pertinent adaptation strategies to enhance social resilience towards the warming climate.